Inorganic Powders Prepared from Fish Scales - Tatiana Safronova; Viktor Vorobyov; Natalia Kildeeva; Tatiana Shatalova; Otabek Toshev; Yaroslav Filippov; Artem Dmitrienko; Olga Gavlina; Olga Chernega; Elena Nizhnikova; Marat Akhmedov; Elena Kukueva; et al. (Ceramics, 2022)
A mixture of abramis brama (freshwater bream), carassius carassius (crucian carp), and sander lucioperca (pike perch) scales was used for the preparation of fish scale powder containing constituents of organic and inorganic nature. The mixture of the mentioned fish scales was washed, dried, and ground for the preparation of fish scale powder. Vibration sieving was used to prepare fish scale powder enriched with inorganic components. According to thermal analysis data, this fish scale powder enriched with inorganic components included about 36.5 wt.% components removed when heating, primarily those of organic nature, and 63.5 wt.% mineral components. Inorganic powders consisting of hydroxyapatite and magnesium whitlockite were obtained via heat treatment of this fish scale powder at 800–1000 °C. Particles of these inorganic powders consisted of sintered grains with dimensions less than 100 nm after heat treatment at 800 °C, less than 200 nm after heat treatment at 900 °C, and 100–1000 nm after heat treatment at 1000 °C. Fish scale powder enriched with inorganic components as well as heat-treated inorganic powders consisting of hydroxyapatite and magnesium whitlockite can be recommended for the production of different materials, such as ceramics or composites.